An investigation on factors influencing the rearing and success of biological control agents of Gonipterus sp. n. 2 (Coleoptera: Curculionidae) - Hurley, Brett P. (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2023.